+0  
 
0
233
1
avatar

Can you show me how to solve -g-2=9(g-8)?

Guest Sep 1, 2017

Best Answer 

 #1
avatar+541 
+1

We have the equation -g-2=9(g-8).

Distribute 9 to get -g-2=9g-72.

Subtract 9g to both sides to get -10g-2=-72.

Add 2 to both sides to get -10g=-70.

Divide -10 to both sides to get g= 7.

g= 7, and that's our answer.

Gh0sty15  Sep 1, 2017
 #1
avatar+541 
+1
Best Answer

We have the equation -g-2=9(g-8).

Distribute 9 to get -g-2=9g-72.

Subtract 9g to both sides to get -10g-2=-72.

Add 2 to both sides to get -10g=-70.

Divide -10 to both sides to get g= 7.

g= 7, and that's our answer.

Gh0sty15  Sep 1, 2017

10 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.